Description of the immature stages of Sigara (Tropocorixa) jensenhaarupi (Hemiptera: Heteroptera: Corixidae: Corixini), with ecological notes - María Cecilia Melo; Erica Elizabeth Scheibler (Revista Mexicana de Biodiversidad)
Sigara (Tropocorixa) jensenhaarupi Jaczewski is the smallest species of the subgenus ranging from 4.2-4.7 mm, and it is characterized by the absence of a strigil, the small and narrow genital capsule with a short hypandrium in males, and the shape of the abdominal tergite VII in females. This species is endemic to the Patagonian subregion (Andean region) in Argentina. A monthly sampling study was performed during a year in northern Mendoza, and additional material was collected in southern Mendoza, more precisely from Bañado Carilauquen in the Llancanelo Lake Reserve (Malargüe Department). Since little is known about the ecological requirements of S. (T.) jensenhaarupi, herein we describe its habitat, the environmental conditions and its association with other macroinvertebrates. Also, we provide a morphological description of larval stages, and provide new records of this species.